Dependent growth : foreign investment and the development of the automotive industry in East-Central Europe - Pavlínek, Petr, 1963- (Springer, 2017)
This book offers a critical analysis of recent developments in the automotive industry of East-Central Europe (ECE). Economists, industry specialists and national governments have considered the rapid development of the automotive industry in ECE in the past twenty years an unqualified success. This rapid growth has been based on large inflows of foreign direct investment (FDI) from Western Europe, North America, Japan and South Korea, and it significantly contributed to GDP growth, created thousands of new jobs, and completely transformed the previously existing automotive industry in the region. This volume offers an analysis that goes beyond uncritical celebratory accounts of this rapid growth. It is based on original, detailed firm-level research conducted by the author in Czechia and Slovakia between 2009 and 2015 that covered assembly firms and the networks of component suppliers. Theoretically and conceptually, the analysis will draw on the global production networks and global value chains perspectives. Drawing on the original empirical data and on additional available information, this volume concentrates on several important questions related to the development of the automotive industry in ECE in the 2000s: " The role of FDI in the rapid development of the automotive industry after 1990 and particularly in the 2000s." The upgrading of the automotive industry in East-Central Europe through FDI " The position of ECE in the automotive industry research and development (R & D) " The effects of the 2008-2009 economic crisis in the automotive industry of ECE." The role of state in the rapid development of the automotive industry in ECE in the 1990s and 2000s." The effects of FDI on domestic firms in the form of linkages between foreign-owned and domestic firms and spillovers from foreign-owned to domestic firms.
Keywords: Automobile industry and trade -- Europe, Eastern.; Automobile industry and trade -- Europe, Central.; Investments, Foreign.; Central Europe.; Eastern Europe.; elektronické knihy; electronic books